Birth weight increases with birth order despite decreasing maternal pregnancy weight gain. (15th October 2020) - Bohn, Claudia; Vogel, Mandy; Poulain, Tanja; Spielau, Ulrike; Hilbert, Cornelia; Kiess, Wieland; Körner, Antje
Abstract: Aim: We investigated whether birth order is an influencing factor for birth weight independent from maternal factors. Methods: Data were obtained from the longitudinal cohort study LIFE Child and included 1864 children, of which 526 were only children. The 1338 siblings were ranked into first‐borns (n = 570), second‐borns (n = 606) and third‐or‐later‐borns (n = 162). Children born prematurely, suffering from chronic or syndromic diseases, were excluded. We performed intra‐family comparisons to reduce bias and assessed the impact of perinatal parameters, such as birth order on birth weight, using mixed models. Results: Birth weight increased with birth order. In univariate analyses, birth order had a significant effect on birth weight‐SDS with second‐borns having 0.29 SDS (app. 130 g) and third‐borns 0.40 SDS (app. 180 g) higher values than first‐borns ( P < .001). Maternal pregnancy weight gain was associated with higher birth weight‐SDS ( P < .01) in univariate analysis, though maternal pregnancy weight gain was lower for higher birth orders. Multivariate analyses revealed that being a second or third‐or‐later‐born child had a stronger impact on birth weight than all maternal factors. Conclusion: Birth order must be considered a potential risk factor for higher birth weight. Maternal pregnancy weight gain is not the driving factor for higher birth weight in siblings.